ANALISIS DETERMINAN YANG MEMPENGARUHI KEPATUHAN IBU TENTANG PEMBERIAN IMUNISASI MEASLES RUBELA PADA BALITA DI PUSKESMAS DELI TUA KABUPATEN DELI SERDANG - KRISTIN NATALIA (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
The purpose of this study was to analyze what determinants influence maternal adherence regarding Measles Rubella immunization in infants. This type of research is quantitative research with cross sectional study design. The population in this study were all mothers who have children under five in the Delitua Health Center with asample size of 36 people. Data collection methods obtained directly from respondents through interviews using interview guidelines (questionnaire). Secondary data were obtained from Obstetric Gynecology records in the midwifery room and the medical records of the Deli Tua Health Center. Data retrieval of information will be done by interviewing Delitua Health Center with a questionnaire that has fulfilled the elements of validity and reliability. The results of this study are factors that greatly affect mothers not giving MR immunization in infants is a factor of family support with a value of 1.397 and information source factors. It is expected that health workers will provide more health information to the public that MR immunization is very important for toddlers to prevent Measles Rubella disease.